Analisis Persepsi Konsumen Terhadap Aspek Bauran Pemasaran (Marketing Mix 7p) Pada Black Cup Coffee Roaster Di Kota Manado - Alboyn Simarmata; Sherly G. Jocom; Rine Kaunang (Sam Ratulangi University, 2022)
This research aims to determine how consumers' perceptions of aspects of the existing marketing mix at Black Cup Coffee Roaster Manado. This research was conducted from March 2022 to June 2022. The data used in this study were primary data and secondary data. Primary data isobtained from direct interviews with consumers using questionnaires, to 60 respondents. Secondary data is obtained from the documents of Black Cup Coffee Roaster. Secondary data was also obtained through the internet using Google Scholar in the form of books, journal articles and theses related to the research topic, namely Consumer Perception Analysis on Aspects of the Marketing Mix (Marketing Mix 7P) at Coffeeshop. The results showed that consumer perceptions of aspects of the marketing mix (Product, Price, Promotion, Place, Process, People and Physical Evidence) on the Black Cup Coffee Roaster were classified as good. In terms of the marketing mix (Product, Process, and People) applied by Black Cup Coffee Roaster, it is classified as very good. In the aspect of the marketing mix (Price, Promotion, Place, and Physical Evidence) it is quite good.